Nutritional security: Holistic animal farming approach for livelihood security and sustainability (Indian Journal of Animal Production and Management, 2017)
A holistic farming system is the need of the hour as the vital resources like land, water; credit and marketing  are becoming scarcer. An integrated farming consists of a range of resource saving practices that aim to  achieve acceptable profits and high and sustained production levels, while minimizing the negative effects  of intensive farming and preserving the environment. Proper utilization of cow dung and urine into manure,  vermin-compost pesticides, ayurvedic preparations etc can not only generate income but also protect the  soil from fertilizers and chemicals besides harnessing the energy and fuel needs of the rural India. Scientific  studies on socio economic impact of different farming systems by the researchers of various disciplines of  sciences is needed to arrive at a broad based agriculture system aiming at the nutritional security of the  small, marginal and landless farm families.
Keywords: Holistic animal farming; Integrated farming system; Livestock Production systems; Nutritional security; Recycling of Livestock waste